Optimization of supercritical-CO2 process for extraction of tocopherol-rich oil from canola seeds. (June 2021) - Sun, Qingrui; Shi, John; Scanlon, Martin; Xue, Sophia Jun; Lu, John
Abstract: Supercritical carbon dioxide extraction (SC–CO2 ) was used to obtain tocopherol-rich oil from canola seeds. The response surface methodology (RSM) with central composite design (CCD) was used to optimize the processing conditions including pressure, temperature, and extraction time to obtain an oil with high concentration of tocopherols and bioactive properties. The effect of co-solvent on the yields of tocopherol-rich oil was also investigated. The results showed that a tocopherol-rich oil was produced by SC-CO2 under the optimized extraction conditions at pressure of 18 MPa, temperature of 70 °C, holding time of 60 min, and extraction time of 30 min, which have eight times higher concentration than the classical extraction method with n-hexane as solvent. Extending extraction time and adding a co-solvent (ethanol) had negative impacts on the tocopherol-rich oils. No significant differences ( p  > 0.05) were observed on the fatty acid compositions of the extracted canola oils by the two different extraction processes of SC-CO2 and traditional solvent extraction. Highlights: The highest tocopherol content was obtained at the optimized extraction parameters of 18 MPa, 70 °C, and 30 min. SC-CO2 provided a 8-fold increase in tocopherol yield compared to traditional solvent extraction. SC-CO2 with co-solvent of ethanol (2.5%–10%) showed negative impact on the yield of tocopherol.